Design suitable punch or die to overcome springback on u-bending - Tuan Abdul Hadi, Tuan Jusoh (2012)
This project deals with the overcoming springback on u bending. Now days, many research and study have been done on a springback. In sheet metal bending, a flat part is bent using a set of punches and dies. The punch and the dies are mounted on a press machine, which control the relative motion between the punch and die and provides the necessary bending pressure. This project is done with simulation of springback using a material of Stainless Steel on U-bending process by using a 1 mm thickness and the size of the specimen is 100 mm x 90 mm. The springback of Stainless Steel sheet was investigated using finite element analysis. Hyperform software is used in this project to simulate the springback of sheet metal in U-bending. The main problem of the bending process is spring-back phenomenon after removing the punch. The aim of this study includes the springback optimization of the part that required U bending processes using the concept of experimental design a suitable punch or dies.